Ineffectiveness of Social Institutions and Violent Conflicts in Nigeria - Ayandeji, Lateef (Governance and Society Review, 2025)
This study explores the complex relationship between ineffectiveness of social institutions and violent conflicts in Nigeria by applying the theoretical lenses of anomie and functionalism. Nigeria’s diverse socio-economic and political landscape is marred by numerous challenges, including corruption, poverty, insecurity, and weak governance, which have led to various forms of violent conflicts over the course of its history. Indeed, the ineffectiveness of social institutions has created an environment where individuals and groups resort to violence as a means to achieve their goals. This study draws on Robert Merton’s anomie theory, which posits that a disconnect between societal goals and means can lead to deviant behavior. It also applies Émile Durkheim’s functionalism theory, which emphasizes the importance of social institutions in maintaining social order. The study also reveals that ineffective social institutions, including economic deprivation, weak governance, corruption, inadequate education, lack of security, and the failure of the healthcare system have contributed to the emergence and persistence of violent conflicts in Nigerian society. This study concludes that the revitalization of the country’s economy will strengthen other institutions and allow them to perform their roles and unburden their responsibilities as prerequisite to the security and development of Nigeria.